Predicting Postoperative Complications in Older Patients Undergoing Head and Neck Microvascular Reconstruction Using the National Quality Improvement Program Risk Calculator - Sebastian Holm, MD; Jenny Löfgren, MD, PhD; Johann Zdolsek, MD, PhD; Juan Enrique Berner, MD, MSc, FRCS(Plast); Fredrik Landström, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Head and neck cancer (HNC) is the seventh most prevalent cancer worldwide, usually requiring a multidisciplinary approach. The National Surgical Quality Improvement Program (NSQIP) risk calculator is a tool for predicting postoperative complications that possibly can help in decision-making, support patient education, and guide the choice between surgical and nonsurgical treatment options. The aim of this study was to assess the reliability of the NSQIP risk calculator as a predictor of postoperative complications following head and neck surgery with microvascular reconstruction. Methods:. This retrospective study included 99 patients diagnosed with HNC who underwent microvascular reconstruction from January 2016 to February 2021. The observed complications were compared with those predicted by the NSQIP calculator. To assess the discriminatory power of the NSQIP estimates, receiver operating characteristic statistics, logistic regression, and the overall Brier score were used. Results:. Forty-four percent of the patients experienced at least 1 postoperative complication, and 27.2% developed serious complications. The receiver operating characteristic analysis for any complications revealed an area under the curve (AUC) of 0.62 (95% confidence interval 0.51–0.73, P = 0.046). For serious complications, the AUC was 0.65 (95% confidence interval, 0.52–0.79, P = 0.021). Both AUC values fell short of the threshold for “acceptable discrimination” (0.7–0.8). The overall Brier score was 0.32, with scores less than 0.09 considered to have good accuracy. Conclusions:. The results suggest that the NSQIP risk calculator tends to underestimate the likelihood of postoperative complications in patients who are undergoing resection for HNC accompanied by microvascular reconstruction.